In-situ study of particle dynamics influenced by gasification reaction in an impinging entrained-flow gasifier - Wang, Yue; Gong, Yan; Wu, Yue; Lu, Hantao; Guo, Qinghua; Song, Xudong; Yu, Guangsuo (Fuel (Guildford), 2025)
•The in-situ visualization of the plug flow zone is realized for the first time.•Particle morphology changes with particle reaction, affecting particle motion.•Volatiles’ release alters particle motion, with short delay from release to ignition.•When slip velocity is low, the volatile flame oscillate along with particle rotation.•The rotation of particles enhances the reaction intensity of volatile combustion. The particle dynamics inside the impinging entrained-flow gasifier have a significant impact on gasification performance. This paper investigates the in-situ particle dynamic behaviors influenced by particle reaction and specific flow filed within the gasifier based on a bench-scale entrained-flow coal-water slurry (CWS) gasification platform. Multiple modified image processing methods were employed to obtain the morphology and dynamic parameters, and an advanced algorithm was utilized to integrate particle motion with real-time changes. Particle rotation and flame oscillations amplitude were quantified, and their connection to the reaction intensity was further explored. The results show a notable reduction in particle size as the particles detach from the burner plane. The number of particles adhering to refractory wall increases significantly due to the impingement of flow field on the wall. The particle dynamics are subject to particle morphology and reaction. The particle aspect ratio is predominantly concentrated at 1.5, with a positive correlation between aspect ratio and particle velocity. Particle velocity during volatile combustion is observed to increase as a consequence of devolatilization. The rotation of particles exerts an influence on the oscillation of volatile flames, with this effect becoming more pronounced as the speed of particle motion approaches the rate of gas flow. An increase in particle rotation speed results in enhancement in flame area and reaction intensity. The flow field within the imaging region was reproduced on the basis of both the position of the flame and the trajectory of the particles.